Triple helix DNA model : Relationship in multicultural characteristic of three Southern borders of Thailand - Suparaporn Tuannoi; Yanin Rugwongwan (My University, 2020)
characteristics Three Southern Borders of Thailand
Keywords: Helix (gastropod); Socioeconomic Development in Asia